PENGARUH MODEL PEMBELAJARAN THINK TALK WRITE (TTW) TERHADAP KETERAMPILAN MENULIS SISWA KELAS V DI SD NEGERI 01 SUGIH WARAS - Yuli Faridatun Nadifah; Krisno Budi Prasetyo (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The objective of this study was to examine the impact of the Think Talk Write (TTW) learning paradigm on the writing proficiency of fifth grade students at State Elementary School 01 Sugih Waras, with a particular focus on exposition text.The research employed a quantitative approach, utilizing a pre-experimental design, specifically a one-group pre-test-post-test design.The research sample comprised 21 students, who were selected using saturated sampling.The findings indicated that the TTW model significantly enhanced students' writing abilities. A significant discrepancy was observed between the pre-test and post-test scores (p < 0.05), as indicated by the results of the two-tailed test.The TTW paradigm is structured in three distinct stages: thinking, speaking, and writing. These stages are designed to foster critical thinking, discussion, and systematic expression of ideas. The efficacy of the TTW model in enhancing students' expository text writing skills has been demonstrated.